Printing and prophecy: prognostication and media change, 1450 - 1550 - Green, Jonathan (Cultures of knowledge in the Early Modern World, 2012)
Printing and Prophecy: Prognostication and Media Change 1450-1550 examines prognostic traditions and late medieval prophetic texts in the first century of printing and their effect on the new medium of print. The many prophetic and prognostic works that followed Europe's earliest known printed book---not the Gutenberg Bible, but the Sibyl's Prophecy, printed by Gutenberg two years earlier and known today only from a single page---over the next century were perennial best sellers for many printers, and they provide the modern observer with a unique way to study the history and inner workings of the print medium. The very popularity of these works, often published as affordable booklets, raised fears of social unrest. Printers therefore had to meet customer demand while at the same time channeling readers' reactions along approved paths